Strategi Pemberian Reward dalam Menumbuhkan Motivasi Belajar pada Mata Pelajaran Matematika Peserta Didik Kelas I SD Negeri 22 Koto Baru Solok - Laila Marhayati; Pinta Medina (Departement of Mathematics Education, 2023)
The aims of this research were: (1) to find out the implementation of reward strategies in increasing students learning motivation in mathematicc in class I SDN Koto Baru Solok, (2) to find out the inhibiting factors for implementing reward strategies in increasing students learning motivation in mathemaics subject in class I SDN Koto Baru Solok, (3) knowing the implications of reward strategies in increasing student learning motivation in mathematics in class I SDN 22 Koto Baru Solok. To achieve this goal, researchers use a type of qualitative research, this qualitative research has the goal of understanding the phenomena experienced by research subjects. The type of research that the researchers used in this study was a type of interview and observation reserarch, where the researcher tried to find out how the strategy of giving reward in increasing students motivation in maathematics in class I SDN 22 Koto Baru Solok. The results of this study illustrate that this reward strategy has a positive impact on students learning motivation in mathematics in class I SDN 22 Koto Baru Solok, students try to listen to the explanations given by the teacher well so they can complete the assignments given properly. Quickly and correctly so that they can get the reward that has been provided by the teacher.